Analisis Penggunaan AI dalam Keberhasilan Customer Experience Pengguna Aplikasi E-Commerce Shopee - Arief Zikry; Muhammad Bitrayoga; Siska Yulia Defitri; Akhmad Dahlan; Nina Dwi Putriani (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
E-commerce has experienced rapid growth with the adoption of digital technology particularly in Southeast Asia. AI enables Shopee to provide personalized product recommendations, responsive customer service, and secure shopping experiences. This study analyzes the use of Artificial Intelligence (AI) technology in enhancing user experience on the Shopee e-commerce platform. The research employs a mixed-method approach involving 400 Shopee users in Indonesia. Product recommendation and user experience personalization both significantly increase user satisfaction. User experience personalization has a greater influence than product recommendations in increasing user satisfaction. The implications of this study suggest that AI not only enhances Shopee's operational efficiency but also strengthens customer satisfaction and loyalty, making it a key element in maintaining competitiveness in today's competitive e-commerce industry